2012
DOI: 10.1111/j.1440-0960.2012.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic pemphigus

Abstract: Paraneoplastic pemphigus (PNP) is a distinct autoimmune blistering disease that can affect multiple organs other than the skin. It occurs in association with certain neoplasms, among which lymphoproliferative diseases are most commonly associated. The clinical presentation of PNP consists typically of painful, severe oral erosions that may be accompanied by a generalised cutaneous eruption and systemic involvement. The eruption may be of different morphology, consisting of lesions that resemble pemphigus, pemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 50 publications
1
103
0
6
Order By: Relevance
“…The autoimmune skin disorders pemphigus and paraneoplastic pemphigus are associated with the presence of circulating autoantibodies attacking desmosomal components including Dsg1, Dsg3, Dsc3, and possibly Pkp3, bullous pemphigoid antigen 1, envoplakin, periplakin, and Perp (Koulu et al 1984;Amagai et al 1991;Nguyen et al 2009;Mao et al 2010;Yong and Tey 2012;Kalantari-Dehaghi et al 2013) and reviewed recently by several groups (Amagai and Stanley 2012;Grando 2012;Cirillo and Al-Jandan 2013). Although a potential role for antibodies directed against cytoplasmic components in disease pathogenesis has been suggested, the majority of data point to Dsg3 and Dsg1 as the primary targets in pemphigus vulgaris and foliaceus (see Fig.…”
Section: Desmosomes In Epidermal Autoimmune Disorders and Under Attacmentioning
confidence: 99%
“…The autoimmune skin disorders pemphigus and paraneoplastic pemphigus are associated with the presence of circulating autoantibodies attacking desmosomal components including Dsg1, Dsg3, Dsc3, and possibly Pkp3, bullous pemphigoid antigen 1, envoplakin, periplakin, and Perp (Koulu et al 1984;Amagai et al 1991;Nguyen et al 2009;Mao et al 2010;Yong and Tey 2012;Kalantari-Dehaghi et al 2013) and reviewed recently by several groups (Amagai and Stanley 2012;Grando 2012;Cirillo and Al-Jandan 2013). Although a potential role for antibodies directed against cytoplasmic components in disease pathogenesis has been suggested, the majority of data point to Dsg3 and Dsg1 as the primary targets in pemphigus vulgaris and foliaceus (see Fig.…”
Section: Desmosomes In Epidermal Autoimmune Disorders and Under Attacmentioning
confidence: 99%
“…Different kind of lesions may coexist and evolve from one type to another [3,40] . Cutaneous lesions could be similar to those seen in pemphigus, pemphigoid, erythema multiforme or graft versus host disease [11,38,40] . Pustular and psoriasis form presentation have also been described [3] .…”
Section: Clinical Featuresmentioning
confidence: 86%
“…Nearly 84% of all PNP are found in association with hematologic neoplasms or disorders [2,6] . Among these, non-Hodgkin's lymphoma accounts for 38.6%, chronic lymphocytic leukemia for 18.4%, Castleman's disease for 18.4%, thymoma for 5.5%, Waldenstrom's macroglobulinemia for 1.2%, Hodgkin's lymphoma for 0.6%, and monoclonal gammopathy for 0.6% [2,5,6,11] . In addition, carcinomas developed from epithelial cells (8.6%) [12][13][14] , sarcomas derived from mesenchymal lines (6.2%) [9,15,16] , and melanoma (0.6%) [17] also are reported in association with PNP.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis is thought to be due to the production of antibodies against tumor‐derived antigens; the antibodies may attack components sharing the same or a similar epitope 8. Wang et al 9 reported that MG is a complication of PNP.…”
Section: Discussionmentioning
confidence: 99%